Doing working-class history
1 online resource
Keywords: "Economic and political uncertainty has brought the language of class-especially discussion of the working class-to a broad audience across scholarship and social debate. This introductory volume shows how the history of the working class has, is, and can be researched, written, and represented. The book is structured in three parts: Perspective, Context, and Application. Each offers an introduction to both classic historiography and new ideas and methodologies. With chapters covering a span of the years c.1750 - present, the book focuses on three essential questions: 1. What is working-class history and what should it become? 2. What can a focus on working-class history reveal? 3. What are the possibilities of this research in the University classroom, the heritage world, and beyond? Doing Working-Class History will appeal to students and scholars of working-class history, whether relative newcomers to the field or veteran researchers interested in new approaches and material. It will also be of interest to local and family historians, museum and heritage professionals, and general readers"--